Pengaruh Good Corporate Governance terhadap Kinerja Keuangan Perusahaan - Helin Titania; Salma Taqwa (Universitas Negeri Padang, 2023)
This study aims to determine the effect of good corporate governance on financial performance. The independent variable in this study is good corporate governance which is proxied to be an independent board of commissioners, audit committee, and managerial ownership, while the dependent variable of this study is financial performance which is proxied by Tobin's Q. The subject of this study is BUMN companies, with the study population being all BUMN companies listed on the Indonesia Stock Exchange. The type of data used is secondary data in the form of annual financial reports of BUMN companies listed on the Indonesia Stock Exchange in the period 2019-2021. The technique used for sampling is the purposive sampling and the method used for hypothesis testing is multiple linear regression analysis. The results showed that the independent board of commissioners variable had a significant positive effect on financial performance, the audit committee had no effect on financial performance, and managerial ownership had no effect on financial performance.